Detecting irregularities in Russian economic statistics - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
In addition to increased uncertainty related to Russian statistics since the invasion of Ukraine, some observers have raised doubts about the quality of Russian statistics. Applying simple analytical tools to detecting irregularities in Russian economic data that could implicate data manipulation, our analysis reveals irregularities and confirms the increased uncertainty related to Russia's post-invasion statistical data. We find, however, no compelling evidence of extensive systematic data manipulation. Therefore, it would be risky to assume that the Russian statistics deliberately paint an overly rosy picture of economic conditions.
urn:nbn:fi-fe2024102486929
Keywords: 330; Russia; economy; statistics